Optimasi Keamanan Instant message pada Sistem Operasi Android - mukhlison st; Sholeh Hadi Pramono; Onny Setyawati (Fakultas Teknik, Universitas Brawijaya, 2015)
In this study AES and Kerberos is used to optimize the security system on instant message so that a text message is sent securely through on goal. The addition and incorporation of AES with Kerberos is used to improve the efficiency of security primarily on user authentication and file encryption text message. The test results showed a AES and kerberos able to optimize the security system instant message. Percentage of instant message security system applications in the study reached 95 %, derived from the percentage of test data and the success rate error test results. AES - 256 had 14 round keys with a key length of 256 - bits, hence AES encrypted file has a powerful message.